Luis T. Bonmatí, Publio Virgilio Marón Eneida, ilustraciones de Federico Del Barrio, Madrid, Reino de Cordelia, 2023, 744 páginas, ISBN 978-84-19124-46-3 (Minerva, 2025)
Review: Luis T. Bonmatí, Publio Virgilio Marón Eneida, ilustraciones de Federico Del Barrio, Madrid, Reino de Cordelia, 2023, 744 páginas, ISBN 978-84-19124-46-3